Fullerenol-cytotoxic conjugates for cancer chemotherapy - Chaudhuri, Padmaparna; Paraskar, Abhimanyu; Soni, Shivani; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (ACS Nano, 2009)
In the present study, we report the novel application of polyhydroxylated fullerenes (fullerenols) in cancer drug delivery. The facile synthetic procedure for generating multiple hydroxyl groups on the fullerene cage offers scope for high drug loading in addition to conferring hydrophilicity. Doxorubicin, a first line cancer chemotherapeutic, was conjugated to fullerenols through a carbamate linker, achieving ultrahigh loading efficiency. The drug-fullerenol conjugate was found to be relatively stable in phosphate buffer saline but temporally released the active drug when incubated with tumor cell lysate. The fullerenol-doxorubicin conjugate suppressed the proliferation of cancer cell-lines in vitro through a G2-M cell cycle block, resulting in apoptosis. Furthermore, in an in vivo murine tumor model, fullerenol-doxorubicin exhibited Comparable antitumor efficacy as free drug without the systemic toxicity of free doxorubicin. Additionally, we demonstrate that the fullerenol platform can be extended to other chemotherapeutic agents, such as the slightly water-soluble cisplatin, and can emerge as a new paradigm in the management of cancer.
Keywords: chemotherapy; doxorubicin; drug delivery; fullerenol; nanoparticle

Coupling growth-factor engineering with nanotechnology for therapeutic angiogenesis - Roy, Rituparna Sinha; Soni, Shivani; Harfouche, Rania; Vasudevan, Pooja R.; Holmes, Oliver; de Jonge, Hugo; Rowe, Arthur; Paraskar, Abhimanyu; Hentschel, Dirk M.; Chirgadze, Dimitri; Blundell, Tom L.; Gherardi, Ermanno; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Therapeutic angiogenesis is an emerging paradigm for the management of ischemic pathologies. Proangiogenic Therapy is limited, however, by the current inability to deliver angiogenic factors in a sustained manner at the site of pathology. In this study, we investigated a unique nonglycosylated active fragment of hepatocyte growth factor/scatter factor, 1K1, which acts as a potent angiogenic agent in vitro and in a zebrafish embryo and a murine matrigel implant model. Furthermore, we demonstrate that nanoformulating 1K1 for sustained release temporally alters downstream signaling through the mitogen activated protein kinase pathway, and amplifies the angiogenic outcome. Merging protein engineering and nanotechnology offers exciting possibilities for the treatment of ischemic disease, and furthermore allows the selective targeting of downstream signaling pathways, which translates into discrete phenotypes.
Keywords: cardiovascular disease; HGF/SF; ischemic disease; nanoparticle; protein engineering